Tanah Adat Orang Sarmi: Pola Kepemilikan, Pengelolaan dan Pemanfaatan Sumber Daya Alam - Untung, Bambang Wuragil (JURNAL EKOLOGI BIROKRASI, 2022)
This article aims to examine the adaptation of the Isirawa tribe, the Isirawa tribe, the Betaf tribe, the Manirem tribe, the Mawes tribe, the Rumbuai tribe, and the Sawar tribe, the Sobey tribe in Sarmi Regency, Papua Province with a system of ownership, management, and utilization of natural resources of customary land. they have. The theory used to analyze the data is the Structural-Functional theory. While the method used is a qualitative approach by analyzing qualitative data accurately with a conceptual framework based on phenomena that occur to recommend theoretical and pragmatic concepts. Data collection techniques used are library research, interviews and field observations. The Isirawa, Betaf, Mawes, and Sawar tribes have cultural values that govern their relationship with their Creator, their relationship with others and their relationship with the environment, namely land and natural resources. This value regulates the value of customary land, patterns of ownership, management, and use, which are still strong to sustain their life, even though many have clashed with cultures from outside their tribe. Knowledge of the 4 tribes and cultural values, norms, rules, laws and customs, has governed the pattern of ownership, management, and utilization of natural resources on their customary lands, and also serves to change or develop things that are adaptive to ownership patterns, management, and utilization of available customary land natural resources.